Dakwah Berbasis Pemberdayaan Ekonomi dan Peningkatan Kesejahteraan Madâu - Setiawan, Asep Iwan (Jurnal Ilmu Dakwah, 2012)
Dompet Peduli Umat (DPU) Daarut Tauhid exists around people through Desa Ternak Mandiri (DTM) program as a concern in poverty. DTM program conducted by the DPU has a unique character which using this approach in doing poverty alleviation mission. This phenomena indicates that the DPU has contributed to the community to improve the welfare of people who are categorized as a poor. With typical propaganda materials that can motivate and help people who are economically weak to grow and be empowered so they can live independent economically and spiritually as well. This program succeed to increase such as family income, a better understanding of the religious, and scientific livestock management. These sciences and experiences are very useful to them to support life after the program is completed. This program is run by zakat funds raised by the charity as well as active participation DPUâs companion activities that comprise the religious field assistance, animal healthcare assistance deployed at the Desa Ternak Mandiri at Cimenyan - Bandung.